PEMBERIAN TERAPI MURATTAL AL-QURAN TERHADAP KUALITAS TIDUR IBU HAMIL PRIMIGRAVIDA TRIMESTER III - Noviyanti Noviyanti; Rahmi Rahmi; Ratna Dewi; Nurdahliana Nurdahliana (Program Studi Kebidanan Fakultas Kedokteran Universitas Malahayati, 2021)
GIVING MURATTAL AL-QURAN THERAPY ON QUALITY TRIMESTER PRIMARY PREGNANT MOTHER'S SLEEP III Background : Expecting mothers experienced different discomforts which were frequently felt in the third trimester, a waiting period in which the pregnant mothers started to be alert of delivering a baby. These discomforts resulted in disturbance of activities of the expectants. Sleep problem was mostly occured during this trimester which might decrease sleep quality. To overcome the complaint, there should be a way to increase sleep quality of the pregnant women. One of them is Murattal Qur'an.Purpose : This study was aimed at finding out the effect of Murattal Qur'an on third semester toward sleep quality of the pregnants.Methods : This research belonged to a quasi-experimental with a pretest-posttest control group design. The population in this study were all pregnant women in the third trimester primigravida in the working area of the Kuta Baro Health Center, Aceh Besar. The sample was 40 pregnant women who were divided into the control group and the treatment group. The treatment group listened to the Murattal Quran chapter Ar-Rahman on Android for 7 nights before going to bed. Data was analysed by using the Wilcoxon test because the data were not normally distributed.Results : The obtained significant value (p) of the treatment group of before and after therapy was 0.000 lower than 0.05 (p=0.000 <0.05)Conclusion : There is an effect of giving Murattal Al-Quran therapy in the third trimester primigravida on the quality of mother's sleep.Suggestion : It hoped that it increased the active role of Midwives to provide information to pregnant women about the way to overcome the sleep disorders of the third trimester pregnant women was by by listening to the murattal Quran. Keywords: Murattal Al-Quran, Sleep Quality, Primigravida, Third Trimester.ABSTRAK Latar Belakang : Ketidaknyamanan yang dirasakan oleh ibu hamil paling sering dirasakan saat trimester III. Trimester III merupakan masa menunggu kelahiran bayinya. Ketidaknyamanan yang dirasakan ibu mengakibatkan aktivitas sehari-hari ibu hamil menjadi terganggu. Gangguan tidur merupakan Keluhan yang paling sering terjadi pada ibu hamil trimester III. Gangguan ini menyebabkan kualitas tidur ibu menurun. Salah satu cara pendekatan untuk meningkatkan kualitas tidur ibu hamil adalah mendengarkan lantunan ayat Al-Quran.Tujuan : Mengetahui pengaruh pemberian terapi murattal Al-Quran pada primigravida trimester III terhadap kualitas tidur ibu.Metode : Jenis penelitian adalah quasi-eksperimen dengan pendekatan pretest-posttest control group design. Populasi adalah primigravida trimester III di wilayah kerja Puskesmas Kuta Baro Kabupaten Aceh Besar. Jumlah sampel 40 ibu hamil yang dibagi menjadi kelompok kontrol dan kelompok perlakuan. Kelompok perlakuan mendengarkan murattal Al-Quran surah Ar-Rahman dengan menggunakan HP Android selama 7 malam sebelum tidur. Analisa data menggunakan Uji Wilcoxon karena data berdistribusi tidak normal.Hasil : Nilai signifikan pada kelompok perlakuan terhadap kualitas tidur ibu sebelum dan sesudah diberikan terapi adalah p = 0,000 lebih kecil dari nilai 0,05.Kesimpulan : Terdapat pengaruh pemberian terapi murattal Al-Quran pada primigravida trimester III terhadap kualitas tidur ibu.Saran : Meningkatkan peran aktif bidan dalam memberikan informasi kepada ibu hamil tentang asuhan ketidaknyaman ibu hamil trimester III yaitu masalah gangguan tidur dengan mendengarkan murattal Al-Quran. Kata Kunci: Murattal Al-Quran, Kualitas tidur, Primigravida, Trimester III.